Promoting Petra Language Center To Its Target Market By Using A Website - Agnes Emmilia Eka Rosanti (Institute of Research and Community Outreach - Petra Christian University, 2021)
I did my internship in Petra Language Center. The Products of PLC are English Language Center, Mandarin Language Center, Japanese Language Center, French Language Center, and Dutch Language Center. For English Language Center, it has other courses and it will be explained in Creative Thesis. The target market is children, teenagers, and general adults who want to enhance their foreign language skill. The competitors of PLC are Ubaya Language Center and Unesa Language Center. The main problem of PLC is that the customers do not know where to go to get the information. The solution to this problem is to make a website. Website is a right tool for PLC because it is accessible and it provides the specific information about courses in PLC. The benefits of PLC website are to increase sales and profit, to expand its market, and to build the relationship with the customers. Keywords : promotional tool, website, unique selling point